Proceedings of the 5th Symposium on the Dynamics and Control of Single-track Vehicles: Bicycle and Motorcycle Dynamics 2023, October 18-20, Delft, The Netherlands (TU Delft OPEN Books, 2024)
The Bicycle and Motorcycle Dynamics (BMD) Conference is held every three years. The first conference was held in Delft, The Netherlands in 2010. The aim of this symposium is to bring together leading scientists and researchers in the field of bicycle and motorcycle dynamics and control, in a broad sense. Topics include but are not limited to: single track vehicles (e.g. bicycles, motorcycles, scooters), narrow track and tilting vehicles, unicycles, dicycles (e.g. Segways and hoverboards), modeling, kinematics and dynamics, control, human control, rider properties, handling qualities, tires, experiments, aerodynamics, simulators, nonholonomic dynamics, robot riders, path following. For an open sharing of information, the meeting is organized to provide as much interaction between participants as possible. The format is informal and fluid, with a single track of presentations and extensive time scheduled for interaction, and the forming and sharing of ideas.